2017
DOI: 10.3390/ma10020097
|View full text |Cite
|
Sign up to set email alerts
|

Gold Nanoparticles in Photonic Crystals Applications: A Review

Abstract: This review concerns the recently emerged class of composite colloidal photonic crystals (PCs), in which gold nanoparticles (AuNPs) are included in the photonic structure. The use of composites allows achieving a strong modification of the optical properties of photonic crystals by involving the light scattering with electronic excitations of the gold component (surface plasmon resonance, SPR) realizing a combination of absorption bands with the diffraction resonances occurring in the body of the photonic crys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(47 citation statements)
references
References 161 publications
0
43
0
Order By: Relevance
“…In order to excite the surface plasmons, optical elements, such ashigh refractive index prism, optical fiber, and diffraction grating, are utilized [10]. SPR-based optical sensors are employed for different applications in life sciences, environmental safety, electrochemistry, biomedical diagnostics and chemical sciences [11]. In this work, the main purpose was to design and implement an optical fiber as a chemical sensor based on surface plasmon resonance.…”
Section: Issn: 0067-2904mentioning
confidence: 99%
“…In order to excite the surface plasmons, optical elements, such ashigh refractive index prism, optical fiber, and diffraction grating, are utilized [10]. SPR-based optical sensors are employed for different applications in life sciences, environmental safety, electrochemistry, biomedical diagnostics and chemical sciences [11]. In this work, the main purpose was to design and implement an optical fiber as a chemical sensor based on surface plasmon resonance.…”
Section: Issn: 0067-2904mentioning
confidence: 99%
“…These results confirm the potential of IO materials as light harvesting catalysts for solar hydrogen production, arising from decreased electron/hole recombination rates and their ability to function at different orientations corresponding to different angular distributions of sunlight. Our future research will focus on the role of localized surface plasmon resonance (LSPR) in PBG materials with nanostructured Au layers, as the merits of combining PBG materials and LSPR is a current area of interest 10 and we have recently shown that LSPR can increase photocatalytic reaction rates. 11…”
Section: Catalystmentioning
confidence: 99%
“…[15]. Today, SPR-based optical sensors are employed for different applications in life sciences, electrochemistry, environmental safety, and biomedical diagnostics, as illustrated in Figure 1 [16,17]. SPR is a promising and powerful optical detection technique for studying label-free biomolecular interactions in real time within a variety of diverse biomedical applications due to the label-free sensing, fast response, and high sensitivity [18][19][20].…”
Section: Introductionmentioning
confidence: 99%